2009
DOI: 10.1111/j.1538-7836.2009.03606.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell specific adhesion molecule (ESAM) localizes to platelet–platelet contacts and regulates thrombus formation in vivo

Abstract: Summary Background In resting platelets, endothelial cell specific adhesion molecule (ESAM) is located in alpha granules, increasing its cell surface expression following platelet activation. However, the function of ESAM on platelets is unknown. Objective To determine whether ESAM has a role in thrombus formation. Methods and results We found that following platelet activation ESAM localizes to the junctions between adjacent platelets, suggesting a role for this protein in contact-dependent events that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 36 publications
(61 reference statements)
3
52
0
Order By: Relevance
“…Gas6 produced by ECs was recently shown to influence venous thrombus formation through downregulation of TF expression. 46 Like BAMBI, other transmembrane proteins expressed in platelets and the endothelium can modulate thrombus growth and/or stability including platelet endothelial cell adhesion molecule (PECAM-1), 47 endothelial cell-selective adhesion molecule (ESAM), 48 junction adhesion molecule A (JAM-A), 49 and tetraspanin 151, 50 although for all of these, the attributed phenotype is associated with the platelet, rather than endothelial, pool of these receptors. In that regard, BAMBI appears to differ by influencing this process through its role in the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Gas6 produced by ECs was recently shown to influence venous thrombus formation through downregulation of TF expression. 46 Like BAMBI, other transmembrane proteins expressed in platelets and the endothelium can modulate thrombus growth and/or stability including platelet endothelial cell adhesion molecule (PECAM-1), 47 endothelial cell-selective adhesion molecule (ESAM), 48 junction adhesion molecule A (JAM-A), 49 and tetraspanin 151, 50 although for all of these, the attributed phenotype is associated with the platelet, rather than endothelial, pool of these receptors. In that regard, BAMBI appears to differ by influencing this process through its role in the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…37 It may also recruit a protein tyrosine phosphatase such as SHP1 or SHP2, as in the case of ITIM receptors such as PECAM-1, 38 or it may recruit a scaffolding protein such as NHERF-1, as shown in the case of ESAM, a CTX family member, 24 or recruit a negatively regulating kinase such as C-terminal Src kinase, Csk. 37 Several members of the CAM family have been show to exert an inhibitory effect on platelet function.…”
Section: Discussionmentioning
confidence: 99%
“…24 Fetal liver cells were isolated from 14-16 days after coitus and Jam-A gt/gt mice fetuses and injected retro-orbitally into lethally irradiated male Jam-A wt/wt recipients (Cesium-137, 10 Gy, Gammacell 40 Exactor; MDS Nordion). Intravital microscopy experiments were performed as described in the previous section 4 weeks after transplantation.…”
Section: Bm Transplantation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deficiency also increases vascular permeability of the renal glomeruli, resulting in urinary albumin elevation (14). Additionally, it has been shown that ESAM is also expressed on megakaryocytes and platelets (12), where it is involved in the regulation of thrombus formation (15).…”
mentioning
confidence: 99%